(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This study observes that the ability to use a language in a natural setting may be called language proficiency, which plays an important role as a communication tool and an instrument of higher education. The contribution of language in enhancing unity in culturally diverse settings plays a significant role in higher education. Restoring peace and stability can be achieved through proficiency in basic language acquisition skills.